SUSTAINABILITY STRATEGY OF INTEGRATED ORGANIC FARMING BASED ON CIRCULAR ECONOMY IN REALIZING SUSTAINABLE AGRICULTURE AND FOOD SYSTEM - Prajanti, Sucihatiningsih Dian Wisika; Soesilowati, Etty; Lestari, Etty Puji (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
It becomes a dilemma when on the one hand to meet market needs, people massively utilize the environment and on the other hand it causes damage, especially in agriculture. There needs to be an appropriate problem approach to overcome this. The purpose of this research is to develop a strategy model for implementing integrated organic farming based on circular agriculture. This research uses quantitative methods with sequential exploratory design. This design begins with quantitative research first, then qualitative with the aim of completing the discussion with Analytical Hierarchy Process (AHP) analysis. The economic dimension has the greatest weight with a value of 0.381. This indicates that in realizing organic farming integrated with Circular Economy, the first thing that needs to be focused on is the economic dimension by making production cost efficiency (Rank 1; GW 0.118).